2018
DOI: 10.3389/fphys.2018.00154
|View full text |Cite
|
Sign up to set email alerts
|

Integrative Computational Network Analysis Reveals Site-Specific Mediators of Inflammation in Alzheimer's Disease

Abstract: Alzheimer's disease (AD) is a major neurodegenerative disease and is one of the most common cause of dementia in older adults. Among several factors, neuroinflammation is known to play a critical role in the pathogenesis of chronic neurodegenerative diseases. In particular, studies of brains affected by AD show a clear involvement of several inflammatory pathways. Furthermore, depending on the brain regions affected by the disease, the nature and the effect of inflammation can vary. Here, in order to shed more… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…In addition, BF neurons also send projections to the CG (13), and a study revealed that enhancing cholinergic signaling by ACh esterase inhibitor treatment resulted in restoration of cerebral blood flow in the posterior CG, concomitant with improved cognitive function in AD patients (38). A recent study showed an increase in the levels of TNF receptor 1 (TNFR1) in the posterior CG of patients with AD (63), which together with our present results on HLA-DR show an inflammatory profile in AD also in this part of the limbic system.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, BF neurons also send projections to the CG (13), and a study revealed that enhancing cholinergic signaling by ACh esterase inhibitor treatment resulted in restoration of cerebral blood flow in the posterior CG, concomitant with improved cognitive function in AD patients (38). A recent study showed an increase in the levels of TNF receptor 1 (TNFR1) in the posterior CG of patients with AD (63), which together with our present results on HLA-DR show an inflammatory profile in AD also in this part of the limbic system.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies demonstrated that neuroinflammation plays a critical role in the pathogenesis of AD, showing a clear involvement of several inflammatory pathways. 49 NF-κB is a pro-inflammatory transcription factor located in the cytoplasm via binding to the inhibitory IκB protein. IκB is degraded by the proteasome when it is stimulated by pathogens.…”
Section: Discussionmentioning
confidence: 99%